African American Literary History, an Overview in Twenty-Seven Parts (KULT_online, 2011)
The in-depth contributions to the Companion to African American Literature, edited by Gene Andrew Jarrett, attempt to give an overview of African American literary history, outlining its most crucial issues and problems from its genesis in the 18th century during slavery, to post-antebellum literature, the Harlem Renaissance and the 'New Negro', up to the present. Although the essays themselves, written by renowned experts in the field of African American Studies, are of a high quality throughout, the third part of the Companion is flawed by conceptual deficiencies, and thus diminishes the overall positive impression the book leaves.